Human papillomavirus type 18 E2 protein and its effects on differentiation and cell cycle in keratinocytes. - Goh, Belinda Jun Yi. (2010)
High-risk human papillomaviruses (HPVs) are the main etiological agents of cervical cancer. Critical for malignant transformation is the manifestation of the viral E6 and E7 oncogenes, which is associated with viral genome integration and the loss of E2 open reading frame (ORF). The E2 protein is a major regulator of viral DNA transcription and replication, but more recently, it has also been shown to be involved in tumorigenesis for HPV8 in skin cancer. Our work here therefore aims to find suitable conditions in which microarray analyses can be conducted to identify the E2-associated modulations in cellular transcriptome. Using recombinant adenoviruses expressing E2 proteins, we showed that E2 was able to abrogate cell cycle regulations and induce a G2/M arrest in cells that points to a possible cooperation between the E2 and E6/E7 proteins. These cells were found to have supernumerary centrosomes and chromosomal aberrations associated with genomic instability. We also demonstrated that E2 was able to repress certain differentiation markers when expressed in primary human keratinocytes. Altogether, our data have provided intriguing possibilities to the E2-mediated cellular regulations, which strongly suggest its likely role in the modulation of cellular transcriptome that could be vital for transformation and carcinogenic progression.